Методи формування графіних засобів захисту документів - Дурняк, Б.В.; Пашкевич, В.З. (Моделювання та інформаційні технології, 2010)
We worked out the formal description of graphic protection means on the basis of
graphic introduction and rulers of construction and modification of graphic images in
a rectangular coordinate system.